A rapid, sensitive and green analytical method for the determination of sulfite in vinegars using pararosaniline reaction with image detection. Issue 4 (11th January 2018) - Almeida, Pedro L.; Figueiredo do Bonfim, Thais H.; Cunha, Francisco Antonio S.; Lima, Kássio M. G.; Aquino, Jailane S.; Almeida, Luciano F.
Abstract : A green, rapid and sensitive automated analytical method with imaging detection for the determination of sulfite in vinegars using the pararosaniline (PRA)–formaldehyde–sulfite reaction is demonstrated. Abstract : A green, rapid and sensitive automated analytical method with imaging detection for the determination of sulfite in vinegars using the pararosaniline (PRA)–formaldehyde–sulfite reaction is demonstrated. This work proposes the use of a flow-batch analyzer (FBA) in association with digital images (DIs) obtained from a webcam to perform fast and accurate quantification of sulfite in vinegar samples with low waste generation and high sensitivity. The FBA designed for the monitoring of the PRA–formaldehyde–sulfite reaction under non-equilibrium conditions consisted of a mixing chamber (MC) with a lateral glass window and an ultra-bright LED mounted on top of the MC. Rigorous luminosity and time control were required to acquire accurate and precise data from digital images taken during the reaction. An algorithm based on RGB norm vectors (∥ ν RGB ∥) with gamma correction was developed for absorbance calculations. The proposed method was applied to sulfite quantification in five different vinegar samples (apple cider, distilled, lemon, and white and red wine), with iodometric titration as a comparative method. The estimated LOD was 0.04 mg L −1, with a linear range of from 0.13 to 32.7 mg L −1, recoveries were in the range 94–107%, and the sample throughput was 43 h −1 at a reaction time of 30 s. Both the proposed and reference methods were statistically compared using a paired t -test at a confidence level of 95% and the maximum standard deviation was 1.6 and 1.7 mg L −1, respectively. All of the results reported here confirm the proposed method's potential to be a very rapid, low-cost and trustworthy tool, applicable for the quality control of sulfite in a wide variety of vinegar. The low levels of reagent consumption and waste generation in the proposed method qualify the analytical procedure as environmentally friendly and in alignment with green chemistry guidelines.